WHEN CHINESE ADULT CHILDREN DO NOT SUPPORT ELDERLY PARENTS—WHAT WOULD PARENTS DO?. (11th November 2018) - Chou, R
Abstract: China has more than 120 million people age 65 and above—the largest elderly population in the world. In face of a fragmented and incomprehensive social security infrastructure, support from adult children, rooted in filial piety, remains to be the primary form of support for this enormous aging population. However, receiving familial support has become increasingly difficult due to demographic, social, cultural, and economic changes. Given the importance of support from adult children, it is surprising that no systematic studies have examined the recourses of older parents when adult children do not provider support. The present study aims to bridge this gap in our knowledge. Using multinomial logistic regression analyses, this study analyzed data (N = 17, 987) from a nationally representative sample of individuals age 60 and above from the Sample Survey on Aged Population in Urban/Rural China conducted in 2006. Results showed that 47.5% of elders would request the village or neighborhood administrative office to mediate; 29.9% would ask relatives to intervene; 19.1% would simply tolerate and take no action; and 3.6% would sue their children. Elders' age, gender, ethnicity, location of residence (rural vs. urban), education level, financial situation, physical health, Activities of Daily Living (ADL), having close relatives, knowledge about elder rights protection laws, willingness to petition to higher-level government agencies, existence of local elder rights protection associations, and existence of local mediators all play a role in elders' intended choices of action towards non-supportive adult children. The findings have significant implications on theory, policy, and practice.